Bunuh Diri Dalam Perspektif Sosiologi - Alfan Biroli (SIMULACRA: JURNAL SOSIOLOGI, 2018)
Suicide is an event in society that is often inevitable. Suicide is a deliberate end to life. Social symptoms in society greatly affect someone in committing suicide. Referring to Durkheim, there are at least four types of suicide, namely egoistic suicide, suicide altruism, anomie suicide, and fatalistic suicide. Egoistic suicide is a suicide that occurs because social integration is too weak. Suicide altruism is a suicide that occurs because social integration is too strong. Anomie suicide is a suicide that occurs because of the blurring of values and norms in society. Fatalistic suicide is a suicide that occurs because the values and norms that apply in society are too excessive. Suicidal acts that occur in the community can be mapped through the fact that social integration is getting stronger or weaker. In addition, suicide can also be mapped based on the fact that the values and norms are getting weaker or stronger.